Cosmetic potentials of Prunus domestica L. leaves. (28th August 2017) - Stierlin, Emilie; Azoulay, Stéphane; Massi, Lionel; Fernandez, Xavier; Michel, Thomas
Abstract: BACKGROUND: The current study presents new insight on the phytochemical content and biological activities of five Prunus domestica L. varieties ('Quetsche blanche de Létricourt', 'Mirabelle de Nancy', 'Perdrigon violet', 'Mirabelle de Provence', 'Reine‐claude dorée'). RESULTS: The plum leaves were found to possess promising anti‐aging activities by their capacity to inhibit 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH), elastase, hyaluronidase and lipoxygenase. After solid phase extraction (SPE), chlorogenic acid, rutin, quercetin and their derivatives were putatively identified by high‐performance liquid chromatography coupled with tandem mass spectrometry using an electrospray ionization source (HPLC/ESI‐MS/MS). CONCLUSION: The plum leaf, a by‐product, provides an interesting valuable resource for use as a natural cosmetic product or as a food supplement. © 2017 Society of Chemical Industry